Prenatal and early life exposure to air pollution induced hippocampal vascular leakage and impaired neurogenesis in association with behavioral deficits. Issue 1 (December 2018) - Woodward, N.; Haghani, A.; Johnson, R.; Hsu, T.; Saffari, A.; Sioutas, C.; Kanoski, S.; Finch, C.; Morgan, T.
Abstract Exposure to traffic-related air pollution (TRAP) is associated with a range of neurodevelopmental disorders in human populations. In rodent models, prenatal TRAP exposure increased depressive behaviors and increased brain microglial activity. To identify cellular mechanisms, we examined adult neurogenesis and the blood–brain barrier (BBB) in relation to cognition and motivated behaviors in rats that were exposed to a nano-sized TRAP subfraction from gestation into adulthood. At age 5 months, exposed male rats had 70% fewer newly generated neurons in the dentate gyrus (DG) of the hippocampus. Microglia were activated in DG and CA1 subfields (35% more Iba1). The BBB was altered, with a 75% decrease of the tight junction protein ZO-1 in the CA1 layer, and twofold more iron deposits, a marker of microhemorrhages. The exposed rats had impaired contextual memory (novel object in context), reduced food-seeking behavior, and increased depressive behaviors (forced swim). Deficits of de novo neurogenesis were inversely correlated with depressive behavior, whereas increased microbleeds were inversely correlated with deficits in contextual memory. These findings give the first evidence that prenatal and early life exposure to TRAP impairs adult hippocampal neurogenesis and increases microbleeds in association with behavioral deficits.